2021
DOI: 10.1002/ejoc.202100691
|View full text |Cite
|
Sign up to set email alerts
|

Automated Synthesis of Heavily Phosphorylated Peptides

Abstract: Multi phosphorylated peptides are key tools in understanding the biological roles of protein phosphorylation patterns. In this work, we focused on multi phosphorylated peptides with over four, clustered, phosphorylation sites that are termed herein heavily phosphorylated peptides (HPPs). The synthesis of heavily phosphorylated peptides is extremely difficult and requires the use of a wide temperature range. Standard peptide synthesizers are incapable of both cooling and heating, which impedes the automated syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…More efficient control of the temperature, in particular in the Fmoc-deprotection step, allowed the synthesis of peptides bearing up to nine clustered phosphorylations in reasonable yield and purity. 83 Works from Becker and Geyer demonstrated that global phosphorylation could provide access to multiphosphorylated peptides. In their synthesis of silaffin peptides, which play an important role in biomineralization, Lechner and Becker masked serine phosphorylation sites by means of Trt protection.…”
Section: Synthesis Of Phosphopeptidesmentioning
confidence: 99%
“…More efficient control of the temperature, in particular in the Fmoc-deprotection step, allowed the synthesis of peptides bearing up to nine clustered phosphorylations in reasonable yield and purity. 83 Works from Becker and Geyer demonstrated that global phosphorylation could provide access to multiphosphorylated peptides. In their synthesis of silaffin peptides, which play an important role in biomineralization, Lechner and Becker masked serine phosphorylation sites by means of Trt protection.…”
Section: Synthesis Of Phosphopeptidesmentioning
confidence: 99%
“… 13 15 This allowed the synthesis of MPPs with up to nine p-sites with minimal risk of β-elimination byproducts, but the process is very tedious and time-consuming. 18 An average synthesis time of an MPP via one of the above methods ranges from several hours to days depending on the sequence and the phosphorylation pattern and is much slower than the synthesis of nonphosphorylated peptides. 19 , 20 Accelerated SPPS processes are in high demand as peptide libraries are an essential tool for biological studies.…”
mentioning
confidence: 99%
“…The automated approach provides MPPs with five p-sites in crude purity of above 50%, and the targeted approach can provide even higher purities. 15 , 18 Although crude purities obtained by those methods are higher than AMPS, a synthesis of 10 residues in the Glyconeer 2.1 takes ∼14 h, and via the targeted approach it takes days. 15 , 18 This makes the synthesis of each MPP about 40 times longer than via AMPS.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…18 We aimed to automate the optimization of glycosylation temperature using the Glyconeer TM (Scheme 1, bottom). [19][20][21][22] We set three challenges: develop an economically viable protocol to optimize the glycosylation temperature, transfer the optimized conditions from solution phase to solid phase, and decrease the excess of donors used in AGA (Scheme 1 bottom). The design of the strategy relied on these guidelines: (1) The optimization will require a tiny amount of donor and acceptor.…”
mentioning
confidence: 99%